Findings of in vitro Analyses of Basophil Functions May Help Us Better Understand Drug Desensitization - Yamaguchi, Masao; Komiya, Akiko; Suzukawa, Maho; Koketsu, Rikiya; Shiragami, Risa; Iikura, Motoyasu; Nagase, Hiroyuki (Frontiers in Allergy, 2022)
Drug hypersensitivity can be an important problem during pharmacological management of various diseases. Patients diagnosed as having a drug allergy usually need to avoid the offending drug, either temporarily or for life. Another way of overcoming a drug allergy is to establish desensitization using the allergen drug itself. We previously investigated in vitro desensitization of human basophils using a subthreshold dose of an IgE-crosslinking reagent. We found that basophil desensitization occurred in a dose-dependent manner over a period of one to several hours. We think that inducible basophil desensitization occurring without histamine release may explain, at least in part, the clinical features of drug desensitization in type 1 drug allergy.